The strategies bioclimatic importance of applied in architectural design - Mello, Mario Fernando; Santos, Eudes Vinicius dos; Dorneles, Ramires Lunardi; Costa, Grasiele Toneto da; Rosa, Larissa; Dias, Erica Kirchhof (Revista de Administração da UFSM, 2017)
Bioclimatic architecture can be defined as an architecture that brings, in its essence, the climate as an important variable in the design process. Through the use of bioclimatic structures, it is always possible, in a natural way, comfort conditions for the building and consequently for its users, reducing energy consumption. Facing these aspects, the main objective of this work is to identify bioclimatic strategies employed in a building in the city of Itaara, central region of Rio Grande do Sul state, Brazil, based on a climatic characterization of the site and study of the guidelines indicated by the Brazilian standard of comfort , NBR 15220-3. No study has been demonstrated that the implantation of the underground air tunnel and a construction of internal ducts with the objective of producing a crusade added to the placement of double walls and double glazing are the main constructive elements in the model of using bioclimatic strategies. On days when the external temperature exceeds 35ºC, the internal environments of the building are around 25ºC, with the use of ventilation coming from the wind tunnel, showing the efficiency test of bioclimatic technologies.